2019
DOI: 10.1177/1742395319886487
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of how young people experience and perceive living with type 1 diabetes during late adolescence and emerging adulthood

Abstract: Objective Suboptimal glycemic control and psychosocial challenges are significant concerns for adolescents and emerging adults (collectively young people) with type 1 diabetes. Knowledge about young peoples’ attitudes towards living with type 1 diabetes is inadequate, but the issue is important in the development of strategies to improve glycemic control and psychosocial well-being. This study explored young peoples’ perceptions of living with type 1 diabetes. Methods An exploratory, qualitative design was emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(55 citation statements)
references
References 40 publications
10
44
1
Order By: Relevance
“…Daily life is marked by worries for especially parents and siblings, whereas the adolescents take a lighter approach to dealing with life with diabetes and the ensuing risks. This finding contrasts with other studies, which have found adolescents with type 1 diabetes to have day-to-day worries in addition to being worried about long-term issues; participants in one study spoke specifically of constant worries and the fearfulness that goes with worries (Ingersgaard et al, 2019;King et al, 2017). A part of the explanation for this could be that young people are focused on the experience of the present and are living primarily from day-to-day, without devoting much attention to potential future complications.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…Daily life is marked by worries for especially parents and siblings, whereas the adolescents take a lighter approach to dealing with life with diabetes and the ensuing risks. This finding contrasts with other studies, which have found adolescents with type 1 diabetes to have day-to-day worries in addition to being worried about long-term issues; participants in one study spoke specifically of constant worries and the fearfulness that goes with worries (Ingersgaard et al, 2019;King et al, 2017). A part of the explanation for this could be that young people are focused on the experience of the present and are living primarily from day-to-day, without devoting much attention to potential future complications.…”
Section: Discussioncontrasting
confidence: 90%
“…Type 1 diabetes in a family setting alters and disrupts previous family life and entails the entire family perpetually focusing on diabetes and its management. The disruptive nature of diabetes has also been demonstrated in earlier studies (Dickinson & O'Reilly, 2004;Ingersgaard et al, 2019;Marshall et al, 2009) and implied in other studies, such as Dickinson and O'Reilly (2004), who showed that adolescents found it frustrating to carry diabetes supplies around at all times and to have to be prepared for any situation. Kingod and Grabowski (2020) specifically explored the concept of disruption from the perspective of parents of young children with type 1 diabetes and described the notion of chronic disruption, which refers to the state of chronic vigilance parents are in.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations